Optically Unraveling the Edge Chirality‐Dependent Band Structure and Plasmon Damping in Graphene Edges. Issue 22 (17th April 2018) - Duan, Jiahua; Chen, Runkun; Cheng, Yuan; Yang, Tianzhong; Zhai, Feng; Dai, Qing; Chen, Jianing
Abstract: The nontrivial topological origin and pseudospinorial character of electron wavefunctions make edge states possess unusual electronic properties. Twenty years ago, the tight‐binding model calculation predicted that zigzag termination of 2D sheets of carbon atoms have peculiar edge states, which show potential application in spintronics and modern information technologies. Although scanning probe microscopy is employed to capture this phenomenon, the experimental demonstration of its optical response remains challenging. Here, the propagating graphene plasmon provides an edge‐selective polaritonic probe to directly detect and control the electronic edge state at ambient condition. Compared with armchair, the edge‐band structure in the bandgap gives rise to additional optical absorption and strongly absorbed rim at zigzag edge. Furthermore, the optical conductivity is reconstructed and the anisotropic plasmon damping in graphene systems is revealed. The reported approach paves the way for detecting edge‐specific phenomena in other van der Waals materials and topological insulators. Abstract : The edge‐chirality‐dependent graphene plasmonic properties are challenging to identify due to the restricted resolution of standard far‐field methods. In situ infrared images reveal that the edge chirality (zigzag/armchair/bilayer) has a large influence on the electronic band structure and plasmonic damping. By the combination of numerical simulation, the different spatial profiles of optical conductivity at zigzag and armchair edges are reconstructed.